Comparative effectiveness of guided internet-based stress management training versus established in-person group training in employees - study protocol for a pragmatic, randomized, non-inferiority trial - Leif Boß; Peter Angerer; Nico Dragano; David Ebert; Miriam Engels; Elena Heber; Rebekka Kuhlmann; Sascha Ruhle; Christian Schwens; Ines Catharina Wulf; Dirk Lehr (BMC, 2021)
Abstract Background Occupational stress is a major public health challenge that requires a variety of evidence-based preventative approaches to increase their reach within the working population. Behavioral stress management interventions are considered an established approach for occupational stress prevention. Both in-person group-based stress management training (gSMT) and individual Internet-based training (iSMT) have been shown to be effective at reducing stress in employees. However, there remains a lack of evidence on the comparative efficacy of the newer digital format compared to well-established, in-person, group-based training. This study aims (1) to directly compare an evidence-based iSMT with an established gSMT on stress in employees, (2) to analyze the two conditions from a cost perspective, and (3) to explore moderators of the comparative efficacy. Methods In a randomized, controlled, non-inferiority trial employees from the general working population will be allocated to iSMT or gSMT. The primary outcome will be perceived stress, assessed using the Perceived Stress Scale, three months after randomization. The non-inferiority margin for the primary outcome measure will be set at 2 points (Cohen's d = 0.29). This trial will also compare the two interventions from a health economics perspective, and conduct explorative analyses to identify potential effect moderators. Discussion To reach a larger proportion of the working population, well-established gSMT should be complemented with interventions that fit today's society's increasingly digital lifestyle. The current trial will provide evidence supporting the responsible implementation of Internet-based stress management training if the digital format proves to at least be non-inferior to established group-based training. Additional explorative moderator analyses may guide future practices to aid in matching select programs with select users. Trial registration German Register of Clinical Studies (DRKS): DRKS00024892, date of registration: 2021-04-09. Protocol version: 02, 16-10-2021.